2022
DOI: 10.3390/v14071392
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Bronchitis Coronavirus: Genome Evolution in Vaccinated and Non-Vaccinated SPF Chickens

Abstract: Infectious Bronchitis virus (IBV) continues to cause significant economic losses for the chicken industry despite the use of many live IBV vaccines around the world. Several authors have suggested that vaccine-induced partial protection may contribute to the emergence of new IBV strains. In order to study this hypothesis, three passages of a challenge IBV were made in SPF chickens sham inoculated or vaccinated at day of age using a live vaccine heterologous to the challenge virus. All birds that were challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…For example, the IBV GA98 was suggested to have emerged under the immune selection pressure exerted by the use of the DE072 vaccine, and showed fast evolutionary and mutation rates of 2.5% and 1.5% per year, respectively, in the HVR [116] compared to 0.3%-0.6% mutation rate per year for the 793/B genotype in the absence of vaccine use [119]. Under experimental conditions, Flageul et al [120] demonstrated that IBV D388 evolved rapidly over three passages in both unvaccinated chickens and chickens vaccinated with the heterologous vaccine strain H120. However, the viral population selection and genetic drift were completely different in both groups.…”
Section: Diversity and Evolutionmentioning
confidence: 99%
“…For example, the IBV GA98 was suggested to have emerged under the immune selection pressure exerted by the use of the DE072 vaccine, and showed fast evolutionary and mutation rates of 2.5% and 1.5% per year, respectively, in the HVR [116] compared to 0.3%-0.6% mutation rate per year for the 793/B genotype in the absence of vaccine use [119]. Under experimental conditions, Flageul et al [120] demonstrated that IBV D388 evolved rapidly over three passages in both unvaccinated chickens and chickens vaccinated with the heterologous vaccine strain H120. However, the viral population selection and genetic drift were completely different in both groups.…”
Section: Diversity and Evolutionmentioning
confidence: 99%
“…One of the most dangerous viruses that can infect chickens is the avian infectious bronchitis virus, or IBV. In light of this virus, the chicken industry faces difficulties in many regions of the world [1]. The prototypical coronavirus known as the infectious bronchitis virus causes millions of dollars' worth of annual losses for the poultry industry globally [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, novel or variant IBV strains have been frequently isolated following immune failure [ 20 , 21 ]. The selection pressures introduced by the use of vaccines, in addition to those exerted by the infected host microenvironment and physical and biosecurity-associated factors, have caused IBV to evolve rapidly [ 22 ].…”
Section: Introductionmentioning
confidence: 99%